Characterization of ionic liquid cytotoxicity mechanisms in human keratinocytes compared with conventional biocides. (May 2021) - McLaughlin, Martin; Gilea, Manuela A.; Earle, Martyn J.; Seddon, Kenneth R.; Gilmore, Brendan F.; Kelly, Stephen A.
Abstract: The ability to chemically modify ionic liquids (ILs) has led to an expansion in interest in their use in a diversity of applications, not least as antimicrobials and biocides. Relatively little is known about cytotoxicity mechanisms of ILs in comparison to other biocides currently in widespread use, as well as their practical significance for the ecological environment and human health. Using NCTC 2544 and HaCat human keratinocyte cells, this study aimed to characterize cytotoxicity rates and mechanisms of a range of ILs. Using both lactate dehydrogenase (LDH) and 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) based cytotoxicity assays, it was confirmed that at biocide-relevant concentrations, ILs with longer alkyl chains exhibited greater biocidal activity than those with shorter alkyl chains, with comparable activity to the commonly used biocides chlorhexidine, benzalkonium chloride and cetylpyridinium chloride, at relevant in-use biocide concentrations. Mode of cell death, measured using fluorescence-activated cell sorting (FACS) and caspase 3/7 activity, determined necrosis to be the primary cytotoxic mechanism at higher concentrations of the biocides stated above, and with ILs [C14 MIM]Cl and [C14 quin]Br, with apoptosis observed at borderline necrotic concentrations. Perhaps most interestingly, modification of anion had a significant effect on cytotoxicity. The use of N[SO2 CF3 ] as an anion to [C16 MIM] attenuated cytotoxicity 10-fold in comparison to other anions, suggesting cytotoxicity may also be a tuneable property when using ILs as biocides. Graphical abstract: Image 1 Highlights: Cytotoxicity characterised for ionic liquids with antimicrobial potential. Toxicity based on ionic liquid alkyl chain length correlated with common biocides. Cytotoxicity of ionic liquids in human keratinocytes occurs primarily by necrosis. Apoptosis is observed at borderline necrotic concentrations. Changing anion partner in ionic liquids can attenuate cytotoxicity up to ten-fold.